Intra-Parlamentary Political Parties' Behavior in the Candidation Process for Members of Parliament in the 2018-2023 General Elections in Timor-Leste - CARDOSO, Teresinha Maria Noronha; SYARANI, Laurensius P.; ROHI, Rudi (Journal of Tourism Economics and Policy, 2025)
The purpose of this study is to understand the behavior of intra-parliamentary political parties in the process of nominating parliamentary candidates in Timor Leste in the 2018-2023 parliamentary elections. The research method is qualitative with informants from CNE circles, political party members, parliamentary candidates, academics, the press, independent institutions, and the community. The results of the study show competition in political parties so that they do not focus on the interests of the community. The regulatory regulations for submitting female parliamentary candidates are placed in the numbered space between 2-3, one must be a woman and so on, each space is up to 95 prospective parliamentary candidates. However, women are placed in the last numbered space and so on. It is necessary to make changes according to the times because the system is not a dogma in order to continue to exist. However, it remains on the legal path, it must be honest that revisions need to be made. Recruitment of parliamentary candidates focuses on three main criteria: broad insight, mass influence, and economic independence. Political elites should ensure proportional representation from youth and women’s organizations, tribes, districts, intellectuals, and high-electability independents. However, accommodating multiple party interests increases political costs and wastes state funds, leading to voter apathy. Female candidates also face discrimination, often placed last on candidate lists.